Factors affecting dividend policy of listed companies on Vietnam's stock market - Nguyen, Thanh Huyen (H. : ĐHQGHN, 2020)
The relationship between dividend policy and earnings per share, income tax, debt cost, asset size, financial leverage, lag of dividend is analyzed and measured. Based on the regression model, it could be pointed out the positive relationship and negative relationships. From the results of regression model and researches, recommendations are built to suggest companies listed on Vietnam's stock market for the process of dividend policy making.